Dietary docosahexaenoic acid proposed to sensitize breast tumors to locally delivered drug. (April 2010) - Chevalier, Stephan; Goupille, Caroline; Mahééo, Karine; Domingo, Isabelle; Dussiau, Charles; Renoux, Brigitte; Bougnoux, Philippe; Papot, Séébastien
The important factor determining breast cancer outcome is tumor cell sensitivity to cytotoxic agents. Most anticancer drugs lack intrinsic anti-tumor selectivity, provoking adverse effects in healthy nontumor tissues. As a result, drugs cannot always be delivered to the tumor at doses sufficient to induce tumor shrinkage, increasing the risk of the development of cellular drug resistance by tumor cells. Two main approaches are currently being investigated to reduce the toxicity in nontumor tissue by using a prodrug locally delivered through biochemical activation in the tumor environment, and for specifically increasing the sensitivity of tumors to anticancer drugs by modifying the tumor tissue through dietary supplementation. Both approaches have their own limitations that would be alleviated by combining them in order to better treat breast cancers. Specifically, the potential benefit of bringing together a glucuronide prodrug with dietary supplementation using polyunsaturated fatty acids, and in particular the docosahexaenoic acid (22:6n-3), is discussed. This article also addresses the effects of the interaction of docosahexaenoic acid and breast cancer in terms of clinical outcome and mechanistic features.